2015
DOI: 10.1257/aer.20121607
|View full text |Cite
|
Sign up to set email alerts
|

Education, HIV, and Early Fertility: Experimental Evidence from Kenya

Abstract: A seven-year randomized evaluation suggests education subsidies reduce adolescent girls’ dropout, pregnancy, and marriage but not sexually transmitted infection (STI). The government’s HIV curriculum, which stresses abstinence until marriage, does not reduce pregnancy or STI. Both programs combined reduce STI more, but cut dropout and pregnancy less, than education subsidies alone. These results are inconsistent with a model of schooling and sexual behavior in which both pregnancy and STI are determined by one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
225
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(233 citation statements)
references
References 47 publications
6
225
0
2
Order By: Relevance
“…Kirdar, Tayfur, and Koç (2009) use the extension of compulsory schooling in Turkey in 1997 and find that it increased the average age of marriage and reduced fertility at young ages. Duflo, Kremer, and Dupas (2010) provide experimental evidence that access to education for adolescent girls reduced early fertility among girls who were likely to drop out of school. This mixed evidence obviously suggests a lack of consensus regarding the causal effect of women's education on fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Kirdar, Tayfur, and Koç (2009) use the extension of compulsory schooling in Turkey in 1997 and find that it increased the average age of marriage and reduced fertility at young ages. Duflo, Kremer, and Dupas (2010) provide experimental evidence that access to education for adolescent girls reduced early fertility among girls who were likely to drop out of school. This mixed evidence obviously suggests a lack of consensus regarding the causal effect of women's education on fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our article is a theory of economic development since it adds some other components such that corruption, early fecundity, polygamous and social status phenomenon not studied in the standard literature focused on Western countries' marriages evolution. This article introduces to marriages vision in developing countries, specifically in Congo where it is composed of one man versus several women as well as early fertility deeply studied by Kremer and al in Kenya [8]. The article shows that under-development is also caused by women social regression since education is a social promotional engine in income aspect, thus protect against Journal of Human Resource and Sustainability Studies poverty.…”
Section: Loubaki Journal Of Human Resource and Sustainability Studiesmentioning
confidence: 97%
“…They also find that the program partly explains the fertility of women whose children could benefit from it, since women above 25 increased their probability to have a child but decreased their total number of children. Studies that do not exploit natural experiments find more contrasted results: McCrary and Royer (2011) find little impact of early schooling due to a woman's month of birth on early pregnancy in the US, Duflo et al (2015) find that a school subsidy in Kenya decreased early pregnancy, though that effect was reduced for women who were also exposed to an HIV-prevention program.…”
Section: Comparison With Identified Sources Of Fertility Changesmentioning
confidence: 99%
“…Empirical and experimental studies of developing countries have identified three broad factors that affect fertility: access to modern methods of contraception (Goldin and Katz 2002, Bailey 2006, Ashraf et al 2014, Miller and Babiarz 2016, electrification and diffusion of household appliances (Bailey and Collins 2011, Lewis 2013, Grimm et al 2015, and change in education supply or work opportunities (Breierova and Duflo 2004, Jensen 2012, Aaronson et al 2014, Duflo et al 2015, Heath and Mobarak 2015, Lavy and Zablotsky 2015.…”
mentioning
confidence: 99%